Answer: x= -4
Step by step explanation :
−
4
x
+
4
+
x
=
2
(
x
+
12
)
Step 1: Simplify both sides of the equation.
−
4
x
+
4
+
x
=
2
(
x
+
12
)
−
4
x
+
4
+
x
=
(
2
)
(
x
)
+
(
2
)
(
12
)
(Distribute)
−
4
x
+
4
+
x
=
2
x
+
24
(
−
4
x
+
x
)
+
(
4
)
=
2
x
+
24
(Combine Like Terms)
−
3
x
+
4
=
2
x
+
24
−
3
x
+
4
=
2
x
+
24
Step 2: Subtract 2x from both sides.
−
3
x
+
4
−
2
x
=
2
x
+
24
−
2
x
−
5
x
+
4
=
24
Step 3: Subtract 4 from both sides.
−
5
x
+
4
−
4
=
24
−
4
−
5
x
=
20
Step 4: Divide both sides by -5.
−
5
x
−
5
=
20
−
5